2019
DOI: 10.1029/2019je006084
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and Shock Metamorphism of Basaltic Lunar Meteorites Northwest Africa 4734 and 10597

Abstract: We present comprehensive compositional and mineralogical results on two basaltic lunar meteorites Northwest Africa (NWA) 4734 and NWA 10597 to constrain their igneous mineralogy and metamorphic characteristics, and examine the potential pairing relationship among them and other meteorites (e.g., basaltic lunar meteorites collected from LaPaz Icefield, Antarctica (LAPs)). NWA 4734 and NWA 10597 are low‐Ti (3.2–3.5 wt.% TiO2), low‐Al (10–12 wt.% Al2O3), low‐K (880–1,300 ppm K) mare basalts derived from evolved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 57 publications
2
33
1
1
Order By: Relevance
“…Some grains yielding three Raman peaks with the peak positions (~359,~673, and~998 cm −1 , Figure 2 and Table 1) similar to pyroxene, whereas peak widths greater than that of typical crystalline pyroxene, are likely to be tissintite, which was also found in another lunar meteorite (e.g., NWA 4734). [44] The En (100 × Mg/(Mg + Fe + Ca)) and Wo (100 × Ca/(Mg + Fe + Ca)) compositional distribution of pyroxenes in the quadrilateral was obtained using diagnostic Raman peak positions. [40,45] Olivine in NWA 4884 occurs as euhedral/subhedral phenocrysts (~100 μm) or tiny grains in fine-grained matrix.…”
Section: Major Mineralsmentioning
confidence: 99%
“…Some grains yielding three Raman peaks with the peak positions (~359,~673, and~998 cm −1 , Figure 2 and Table 1) similar to pyroxene, whereas peak widths greater than that of typical crystalline pyroxene, are likely to be tissintite, which was also found in another lunar meteorite (e.g., NWA 4734). [44] The En (100 × Mg/(Mg + Fe + Ca)) and Wo (100 × Ca/(Mg + Fe + Ca)) compositional distribution of pyroxenes in the quadrilateral was obtained using diagnostic Raman peak positions. [40,45] Olivine in NWA 4884 occurs as euhedral/subhedral phenocrysts (~100 μm) or tiny grains in fine-grained matrix.…”
Section: Major Mineralsmentioning
confidence: 99%
“…NWA 032 is launch paired with several unbrecciated mare basaltic meteorites-LAP 02205/ 02224/02226/02436/03632/04841 (hereafter LAPs), NWA 4734, and NWA 10597 (Zeigler et al 2005;Day and Taylor 2007;Hill et al 2009;Wang et al 2012;Chen et al 2019). In this section, we compare previous descriptions of shock in NWA 032 to our study.…”
Section: Revised Shock Conditions For Nwa 032 and Paired Basaltic Metmentioning
confidence: 75%
“…In these studies, partial transformation was confirmed by the observation of both optically isotropic and birefringent grains and also by texture, where crystalline igneous plagioclase is highly fractured in contrast to maskelynite which appears as smooth (unfractured) pseudomorphs after precursor plagioclase (Zeigler et al 2005). Plagioclase compositions are highly calcic, overlapping with that of NWA 032, in the range of An 78-90 Ab 10-18 Or 0-4 (NWA 4734;Chen et al 2019), An 78-89 Ab 10-17 Or 0-5 (NWA 10597;Chen et al 2019), and An 84-89 Ab 11-15 Or 0-1 (LAPs;Zeigler et al 2005). Partial amorphization of such calcic plagioclase requires shock pressures on the order of 22-27 GPa (Fig.…”
Section: Revised Shock Conditions For Nwa 032 and Paired Basaltic Metmentioning
confidence: 75%
See 2 more Smart Citations